L’interpellation : interjections et appellatifs. Une approche contrastive italien/français - Carlotta Cini (Corela)
The aim of the present paper is to examine the relationship between interjections and terms of address in certain dialectal forms of address in Italian film dialogs, and how this phenomenon is reproduced in the corresponding versions subtitled in French. Certain particles, called here “vocative interjections” are hybrids between the categories of the address and that of interjections, and they need to be studied as components of the system of address: even though they can be eliminated from a syntactic point of view, they have pragmatic and interactional sense. The corpus is composed by three Italian films; through the analysis of a selection of examples, we will show the consequences of the elimination, in the correspondent French subtitles, of these particles which are usually considered as superfluous, and we will propose some alternative solutions, considering the practical limits of this type of translation.